1982
DOI: 10.1161/01.str.13.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood viscosity parameters and cerebral blood flow.

Abstract: SUMMARY This report describes the statistical relationship of several whole blood viscosity parameters and cerebral blood flow (CBF) in 53 consecutive patients and normal controls. Significant correlations were present between CBF and serum fibrinogen (P = .05), hematocrit (P < .05), and a relationship involving both fibrinogen and hematocrit (P < .01).We conclude that heightened whole blood viscosity does correlate with decreased cerebral blood flow in the ranges measured in our patients, that both fibrinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(92 citation statements)
references
References 36 publications
4
83
0
2
Order By: Relevance
“…These differences in hemodynamic responses may be attributed to the difference in pharmacological action between calcium channel blockers and L-arginine. Blood viscosity is a parameter that defines the blood velocity (45)(46)(47). Therefore, effects on blood viscosity may provide a possible explanation of the difference in pharmacological action between calcium channel blockers and L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in hemodynamic responses may be attributed to the difference in pharmacological action between calcium channel blockers and L-arginine. Blood viscosity is a parameter that defines the blood velocity (45)(46)(47). Therefore, effects on blood viscosity may provide a possible explanation of the difference in pharmacological action between calcium channel blockers and L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…One study found an inverse relation between Hct and cerebral blood flow. 10 Another described a higher baseline Hct value to be independently associated with infarct growth and a lesser chance of successful reperfusion after acute ischemic stroke. 11 Several studies demonstrated a U-shaped relation between outcome parameters and Hct levels, 9,12-14 suggesting an optimal midrange Hct level between 42% and 45%.…”
mentioning
confidence: 99%
“…We interpret this finding in the following way: when studied early, acute-phase responses in stroke patients may be primarily related to events other than the stroke, (e.g., prior infection); beyond 48 hours, acute-phase responses from the stroke itself predominate, resulting in comparable fibrinogen levels for patients with and without infection. Increased fibrinogen levels may contribute to the pathogenesis of cerebral infarction by multiple mechanisms; there is an inverse relation between fibrinogen levels and cerebral blood flow, 32 middle cerebral artery blood velocity in the elderly, 33 cerebral vascular reactivity, 34 and, perhaps, fibrinolytic activity. 35 In addition, fibrinogen serves as the major intercellular link for platelet aggregation via the glycoprotein Ilb-IIIa complex.…”
mentioning
confidence: 99%